SKANDAL DONNER (1900-1902): SEBUAH GERAKAN POLITIK ARSIP: Array - Dharwis Widya Utama Yacob (Arsip Nasional Republik Indonesia, 2014)
Skandal Donner was the event of the taking down of Regents of Madiun, Raden Adipati Brotodiningrat, by the Resident of Madiun, J.J. Donner. It was full of intentionally issues and also with full of debate in the newspapers. The debate in the newspaper pioneered by Tirto Adhi Soerjo in Pembrita Betawi. This scandal appeared uncomfortable situation in the gouvernment of around Java especially East Java, Central Java, and West Java. The regents around Java were worry about their legitimation. Their worry about their legitimation were being demoted as same as Raden Adipati Brotodiningrat. The news about Raden Adipati Brotodiningrat were separated by two sides. One side supported J.J. Donner and the other sides supported Raden Adipati Brotodiningrat. Most of the newspapers which supported J.J. Donner was from Nederlands Newspapers such as De Locomotief and the most newspapers which supported Raden Adipati Brotodiningrat was from indigenous people. archival publication are two kinds of findings aids which have different forms dan function. Nevertheless, users still don’t know the function and how to use guides and archival publication even archivist still not yet understand the different between among those. Political movement is social movement in political aspect. A political movement can organize by individual issues or a lot of issues or one set of concern with social group. A political movement has a goal to ensure citizen and/or civil servants to take an action. A political movement can be local, regional, national, or international. Some of them has to chance about policy such as anti-war movement, ecology movement, and anti-globalizationmovement. A political movement can also to centralize or decentralize nation control, such as anarchism, facism, and nazism. The political movement of archives is one of political movement. The political movement of archives is being pioneered by Tirto Adhi Soerjo which called Skandal Donner.